PSYCHOSOCIAL RISKS: A CRITICAL THEORETICAL PERSPECTIVE ON WORK - Cangussu, Wallace Hugo (Seven Editora, 2026)
This article is an essay that discusses the concepts of psychosocial risks and psychosocial risk factors related to work, addressing, through a critical perspective, the main quantitative theoretical models that propose to analyze them based on stress studies and their limitations. It problematizes the practices adopted by professionals working in the field of Organizational and Work Psychology, pointing out the main contemporary challenges and solutions for an ethical, critical and committed performance in promoting health at the strategic level of organizations. It presents, as alternatives, the main clinical and methodological approaches that constitute the field of work clinics and their relationship with worker health. Finally, it highlights the psychodynamics of work as a theoretical-methodological and critical perspective for the identification of psychosocial risks at work and, above all, as a proposal for intervention to promote organizational changes necessary for the transformation of work situations that generate pathogenic suffering, with consequent illness.